Preparation of a core–shell structured Y@ASA composite material and its catalytic performance for hydrocracking of n-decane. Issue 112 (23rd November 2016) - Yin, Yanchao; Qin, Lihong; Wang, Xiaofeng; Wang, Genggeng; Zhao, Jun; Liu, Baijun; Chen, Yu
Abstract : A series of core–shell structure Y@ASA composites with different content of Y-type zeolite was synthesized in the small-crystal Y zeolite suspensoid by adding CTAB surfactant in the synthesis process of amorphous silica alumina (ASA). Abstract : A series of core–shell structure Y@ASA composites with different contents of Y-type zeolite (abbreviated as Y@A) was synthesized in the small-crystal Y zeolite suspensoid by adding CTAB surfactant in the synthesis process of the amorphous silica alumina (ASA). Y@A composites and their corresponding catalysts were characterized by XRD, SEM, TEM, N2 adsorption–desorption and infrared spectroscopy of pyridine adsorption (Py-IR). The results showed that the surface of the small-crystal Y zeolite was covered uniformly by ASA even if ASA content was only 10 wt%, and more importantly, ASA could provide 3–20 nm mesopores to bring about the formation of the micro- and mesoporous core–shell structured composites with internal microporous Y zeolite and external mesoporous ASA. Furthermore, due to the interaction between ASA and Y zeolite, the hydrothermal stability of the small-crystal Y zeolite was enhanced, and at the same time the acid quantity of the composite was increased. The NiW/USY@A catalysts were synthesized by loading Ni and W on the Y@A. Their hydrocracking and isomerization performance were evaluated by using n -decane as a model compound. The experimental results indicated that the selectivities of the intermediate product and isoparaffin on NiW/USY@A-90 (with 90 wt% Y-type zeolite in the Y@A) are 30.81% and 23.70% higher than NiW/USY-In in which industrial Y was used, respectively. Thus, besides its high hydrocracking performance, NiW/USY@A showed an excellent isomerization capacity.